Monitoring and Analysis of Stress Distribution of the Interaction between Rock and Backfill and the Influence of Geometric Features of the Backfill Boundary - Rong Lu; Fengshan Ma; Jie Zhao; Jianbo Wang; Guilin Li; Bing Dai (Advances in Civil Engineering)
Backfill mining methods are widely used in metal mines. The boundary part of the backfill has a direct effect on the local stability in mining engineering. The distribution of stress on the boundary part of the backfill and surrounding rock had their own features. To study the characteristics of stress distribution of backfill and surrounding rock on the boundary part, we conducted a field investigation, field monitoring, and numerical simulation. According to the underground monitoring, the overall characteristics of the boundary part of the backfill were that the accumulated horizontal stress was larger than the accumulated vertical stress on the deep sublevel and the accumulated horizontal stress was smaller on the shallow sublevel. On the contact zone (i.e., the boundary part), the stress of the surrounding rock was larger than the stress of the backfill. Combined with the numerical model analysis, we determined that the geometric features of the backfill boundary had an influence on the stress distribution of stress. The multistep boundary helped the integrity of the contact zone and local stability in deep mining.